Evaluation of abortions spontaneously induced by Neospora caninum and risk factors in dairy cattle from Lima, Peru - Serrano-Martínez,Marcos Enrique (2019)
Abstract Our objective was to identify the direct and indirect presence of Neospora caninum in dairy cattle and their aborted fetuses from Lima, Peru. A total 219 blood samples obtained from dairy cattle with records of spontaneous abortion were collected to detect antibodies against N. caninum in serum with indirect ELISA and search for risk-factor associations. 68 fetal aborted tissue samples of these cows were analyzed by PCR, indirect ELISA and histopathology assay to detect N. caninum presence. The prevalence ratio (PR) and 95% confidence intervals (CI) were estimated. Univariate analysis was performed using the chi-squared test. Among the 68 aborted fetuses collected, 10 (15%) were positive in at least two diagnostic tests. Among 219 serum samples, 46.6% (95% CI: 40.0%-53.3%) were positive. Cows with 4 years or older (PR: 7.10; 95% CI: 4.89-10.67) and multiparous (PR: 1.76; 95% CI: 1.11-2.80) were found to be more likely to possess N. caninum antibodies. This study detects presence of N. caninum in dairy cattle and their aborted fetus from Lima valley, suggesting biosecurity management improve to neosporosis control.